2017
DOI: 10.12681/mms.1950
|View full text |Cite
|
Sign up to set email alerts
|

New morphological and molecular evidence confirm the presence of the Norwegian skate Dipturus nidarosiensis (Storm, 1881) in the Mediterranean Sea and extend its distribution to the western basin

Abstract: The present study confirms the presence of the Norwegian skate Dipturus nidarosiensis (Storm, 1881) (Stehmann et al., 2015).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(38 citation statements)
references
References 23 publications
(35 reference statements)
8
30
0
Order By: Relevance
“…The record of a juvenile male confirmed the occurrence of D. nidarosiensis in the Strait of Sicily previously assumed by Massi et al (2017) on the basis of a record of one egg capsule found off Pantelleria Island. The presence of the species supports the role of ecological corridor of the Strait of Sicily in connecting organisms living in the western basin (Cannas et al 2010, Follesa et al 2012, Ramírez-Amaro et al 2017 with those distributed in the Ionian Sea (Carbonara et al 2019). The Strait of Sicily is also considered a biodiversity hotspot for cartilaginous fish in the Mediterranean Sea (Enajjar et al 2015, Bradai et al 2018, Di Lorenzo et al 2018) and this new species record strengthens the importance of this area for the conservation of this vulnerable group, as has already been stated in previous studies (Lauria et al 2015).…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…The record of a juvenile male confirmed the occurrence of D. nidarosiensis in the Strait of Sicily previously assumed by Massi et al (2017) on the basis of a record of one egg capsule found off Pantelleria Island. The presence of the species supports the role of ecological corridor of the Strait of Sicily in connecting organisms living in the western basin (Cannas et al 2010, Follesa et al 2012, Ramírez-Amaro et al 2017 with those distributed in the Ionian Sea (Carbonara et al 2019). The Strait of Sicily is also considered a biodiversity hotspot for cartilaginous fish in the Mediterranean Sea (Enajjar et al 2015, Bradai et al 2018, Di Lorenzo et al 2018) and this new species record strengthens the importance of this area for the conservation of this vulnerable group, as has already been stated in previous studies (Lauria et al 2015).…”
Section: Discussionmentioning
confidence: 52%
“…The Strait of Sicily is also considered a biodiversity hotspot for cartilaginous fish in the Mediterranean Sea (Enajjar et al 2015, Bradai et al 2018, Di Lorenzo et al 2018) and this new species record strengthens the importance of this area for the conservation of this vulnerable group, as has already been stated in previous studies (Lauria et al 2015). In addition, the new record of Norwegian skate in the Strait of Sicily points to a wider Mediterranean distribution than previously thought (Ramírez-Amaro et al 2017). Indeed, in the Mediterranean, this species is one of the deepest living skates with records ranging from 600 up to 1400 m (Cannas et al 2010).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…D. nidarosiensis is one of the species that is often misclassified in both the Atlantic and the Mediterranean Basin (Cannas et al, 2010;Follesa et al, 2011;Cariani et al, 2017;Ramírez-Amaro et al, 2017). The geographical distribution of the Norwegian skate D. nidarosiensis is known to occur along the northeast Atlantic, from Iceland, the Faroe Islands and northern Norway to Madeira and northern Mauritania (Stehmann, 1990).…”
Section: Introductionmentioning
confidence: 99%